Motif dan Kepuasan Anak Muda di Kota Denpasar dalam Menonton Channel Youtube Kimi Hime - Permana, I Putu Surya; Sugiarica Joni, Dewa Ayu; Pradipta, Ade Devia (E-Jurnal Medium, 2021)
Kimi Hime is one of the YouTubers who is currently attracting public attention with sexy images game content. This study uses a quantitative descriptive method that aims to find out the motives and satisfied of young people in Denpasar to watch Kimi Hime's YouTube Channel. The data collection technique was done by usingva questionnaire. The results showed that there are three motives that can be satisfied, that is the motive for information, the motive for integrity and social interaction, and the motive for entertainment. The motive that cannot be satisfied is the personal identity motive. Keyword: Young People, Denpasar, Motive, Satisfaction, Youtube Channel, Kimi Hime